If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -1(10y + -3y) = 2 Combine like terms: 10y + -3y = 7y 6y + -1(7y) = 2 Remove parenthesis around (7y) 6y + -1 * 7y = 2 Multiply -1 * 7 6y + -7y = 2 Combine like terms: 6y + -7y = -1y -1y = 2 Solving -1y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-1'. y = -2 Simplifying y = -2
| 3x+2y/3x+y | | x^2+14x+y^2=-4+12y | | 28v^2+16v-44= | | 7x^2-x=7 | | x^2-21x+69=0 | | x^2+10x+87=0 | | 6(7-10x)+3(3-15x)=366 | | 15b^2+25b-40= | | -0.66666666666667x=0.83333333333333 | | -21x^2+95x+6=0 | | 9y+2(6y-5)=53 | | 2x+3c+x+c= | | r(2)-7r+10=0 | | 5x^2-18xy-8y^2= | | (3x)+(x+8)=180 | | 9y+9(14y+2)=288 | | f(x)=6x^2+13x+6 | | 2(x-1)=x-4 | | -8x+5y=7 | | x(2)-x=0 | | 2x^2+3x-7=x^2+5x+39 | | 3(p+9)-12p=51 | | 6-6x+3x=-21 | | 11p=22 | | 5x+10+11x+2+58=360 | | 4x^2+5x=-12 | | 12(m+20)=16m | | x(2)+5x-14=0 | | 8w-30=5w-40 | | 4x^2=-12x-6 | | (x/4)=(x/5)+(7/4) | | 2y-1/21=3y-7/15 |